2018
DOI: 10.1371/journal.pgen.1007519
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA male-specific abdominal plays a critical role in Drosophila accessory gland development and male fertility

Abstract: Although thousands of long non-coding RNAs (lncRNA) have been identified in the genomes of higher eukaryotes, the precise function of most of them is still unclear. Here, we show that a >65 kb, male-specific, lncRNA, called male-specific abdominal (msa) is required for the development of the secondary cells of the Drosophila male accessory gland (AG). msa is transcribed from within the Drosophila bithorax complex and shares much of its sequence with another lncRNA, the iab-8 lncRNA, which is involved in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 76 publications
4
70
0
Order By: Relevance
“…Although the PMR starts normally, the mating‐induced egg‐laying stimulation (Figure E) and the unreceptiveness for a secondary mating (Figure H) is not sustained past the first 2 days post‐mating. This is similar to the PMR seen in mates of iab6 cocu mutant males who similarly also lack all VLCs in the SCs (Figure E) . Although the systematic functional analysis of rab11 was prevented due to general lethality using our driver, we were able to test for the effects of rab7 and rab19 knock‐down.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Although the PMR starts normally, the mating‐induced egg‐laying stimulation (Figure E) and the unreceptiveness for a secondary mating (Figure H) is not sustained past the first 2 days post‐mating. This is similar to the PMR seen in mates of iab6 cocu mutant males who similarly also lack all VLCs in the SCs (Figure E) . Although the systematic functional analysis of rab11 was prevented due to general lethality using our driver, we were able to test for the effects of rab7 and rab19 knock‐down.…”
Section: Resultssupporting
confidence: 71%
“…The association of specific Rabs to maturing VLCs begs the question of whether or not the Rabs are directly required for the formation of the VLCs and SC functionality. Previously, we have shown that the maintenance of the PMR is impaired in mutants that lack all VLCs . Here, we chose to individually knock‐down each candidate rab in SCs and to assay VLC appearance and the long‐term, female PMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It represses the expression of abd‐ A in cis through the process of its transcription, which in turn, affects the activity of cis‐ regulatory elements of abd‐ A and produces a miRNA ( mir‐iab‐8 ) that is encoded by its intron and represses abd‐ A expression . Another lncRNA, msa , which shares much of its sequence with iab‐8 , is required for the development of the secondary cells of the Drosophila male accessory gland . To date, only a few functional aspects related to lncRNA have been reported in other insects.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Another lncRNA, msa, which shares much of its sequence with iab-8, is required for the development of the secondary cells of the Drosophila male accessory gland. 19 To date, only a few functional aspects related to lncRNA have been reported in other insects.…”
Section: Introductionmentioning
confidence: 99%